2021
DOI: 10.1038/s41598-021-83140-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical properties of pretreated coir fiber and fibrous chips reinforced multilayered composites

Abstract: Coir is one of the most important natural fibers having significant potentiality in structural biocomposites production. The long coir fiber (LCF) and short fibrous chips (CFC) were extracted from the husk of coconut. The dimensions of the CFC were within 1.0–12.5 mm and the LCF were within 2.0 mm. All the fibers and fibrous chips were treated with 5% NaOH (alkali) before the biocomposite manufacturing. Different percentages (8%, 10%, and 12%) of melamine-urea-formaldehyde (MUF) were used to produce the tri-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…The defibrated coir fibers were sieved with a sieve analyzer (ANALYSETTE 3Pro, Germany) to produce uniform fibers before biocomposite panel fabrication. Our previous studies provide detailed descriptions of similar sieving protocols for different natural fibers [24,42]. For this test, 100 g coir fibers were randomly selected from the defibrated materials.…”
Section: Coir Fiber Preparation From Coconut Chips and Sievingmentioning
confidence: 99%
See 1 more Smart Citation
“…The defibrated coir fibers were sieved with a sieve analyzer (ANALYSETTE 3Pro, Germany) to produce uniform fibers before biocomposite panel fabrication. Our previous studies provide detailed descriptions of similar sieving protocols for different natural fibers [24,42]. For this test, 100 g coir fibers were randomly selected from the defibrated materials.…”
Section: Coir Fiber Preparation From Coconut Chips and Sievingmentioning
confidence: 99%
“…However, research on coir chips, a byproduct generated during coir fiber processing, is not extensive, particularly not on chips with improved mechanical properties. In our previous study, we reported on the development of coir chips (without extracting into fiber) along with long coir materials reinforced with MUF (melamine-urea-formaldehyde) [24]. However, the internal bonding strengths were less than 0.5 MPa, which, depending on density, is the standard for fiber composite panels.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that thermal conductivity also showing an increasing trends like as mechanical properties with the increased loading of energy reeds in composites system. In our previous study (Hasan et al 2021b) for coir fiber and fibrous chips reinforced with MUF polymeric composite panels (medium density), we have found the thermal conductivity values between 0.09302 ± 00.999 and 0.1078 ± 00.0072 W/(m.K). In another study by Ramanaiah et al (2011) for Typha angustifolia reinforced polyester composites (high density) showed the thermal conductivity between 0.137 and 0.432 W/(mK).…”
Section: Resultsmentioning
confidence: 82%
“…After that, both the rice straw and energy reeds were pretreated with 5% (w/v) of NaOH for removing any impurities present in the raw plant materials. The excessive usage of alkaline reagents could damage the cells of cellulosic substrates (Hasan et al 2021c;Rokbi et al 2011), hence an optimum values of NaOH was used for this pretreatment (Mishra 2003). The materials were soaked in cold water for 24 h at basic pH medium (around 12.0).…”
Section: Preparation Of Rice Straw and Energy Reeds Fibermentioning
confidence: 99%
See 1 more Smart Citation